2001
DOI: 10.1002/bit.10020
|View full text |Cite
|
Sign up to set email alerts
|

Galactomannanases Man2 and Man5 from Thermotogaspecies: Growth physiology on galactomannans, gene sequence analysis, and biochemical properties of recombinant enzymes

Abstract: The enzymatic hydrolysis of mannan-based hemicelluloses is technologically important for applications ranging from pulp and paper processing to food processing to gas and oil well stimulation. In many cases, thermostability and activity at elevated temperatures can be advantageous. To this end, the genes encoding beta-mannosidase (man2) and beta-mannanase (man5) from the hyperthermophilic bacteria Thermotoga neapolitana 5068 and Thermotoga maritima were isolated, cloned, and expressed in Escherichia coli. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
26
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(26 citation statements)
references
References 66 publications
0
26
0
Order By: Relevance
“…Biochemical characterization of Man5C revealed that the optimal temperature of the enzyme was 50 C, and that it was stable up to 45 C for 20 min, whereas the enzyme showed high similarities to thermostablemannanases derived from thermophilic bacteria, such as G. stearothermophilus (optimal temperature: 70 C), 35) T. maritima MSB8 (90 C), 36) and T. neapolitana (92 C) 36) (Table 1). However, the optimal temperature of Man5C was 10 C higher than that of ManA from strain MA-138, which has also been classified in GH5.…”
Section: Discussionmentioning
confidence: 99%
“…Biochemical characterization of Man5C revealed that the optimal temperature of the enzyme was 50 C, and that it was stable up to 45 C for 20 min, whereas the enzyme showed high similarities to thermostablemannanases derived from thermophilic bacteria, such as G. stearothermophilus (optimal temperature: 70 C), 35) T. maritima MSB8 (90 C), 36) and T. neapolitana (92 C) 36) (Table 1). However, the optimal temperature of Man5C was 10 C higher than that of ManA from strain MA-138, which has also been classified in GH5.…”
Section: Discussionmentioning
confidence: 99%
“…The high level of expression of MalE1 in guar gum-grown cells and the ability of MalE1 to bind mannooligosaccharides suggest that the role of MalE1 is to transport oligosaccharides generated from galactomannan hydrolysis. Both endo-1-4-␤-mannanase and ␤-galactosidase are extracellular in T. maritima, so ␤-1-4-linked mannooligosaccharides would be available for transport into cells (24). MalE1 binds only ␤-(134)-mannotetraose and not ␤-(134)-mannobiose and ␤-(134)-mannotriose, showing that it has affinity only for larger mannooligosaccharides.…”
Section: Discussionmentioning
confidence: 99%
“…The results from BLAST program showed homology only in their Nterminal half (amino acid residues 43-201) with -1,4-mannanases (E.C.3.2.1.78), which is derived from Thermotoga neapolitana (27% identity), 9) Arabidopsis thaliana (30%, accession no. CAB82763), Thermotoga maritima (26%), 9) and Aspergillus aculeatus (24%).…”
mentioning
confidence: 99%